2021
DOI: 10.1186/s12951-021-01027-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of biofilm-forming pathogenic bacteria in the presence of nanoparticles and antibiotic: adaptation phenomena and cross-resistance

Abstract: Background Treatment of bacterial biofilms are difficult and in many cases, expensive. Bacterial biofilms are naturally more resilient to antimicrobial agents than their free-living planktonic counterparts, rendering the community growth harder to control. The present work described the risks of long-term use of an important alternative antimicrobial, silver nanoparticles (NAg), for the first time, on the dominant mode of bacterial growth. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…Singh et al [ 35 ] used AgNPs with a size of 20–40 nm and noted that the MIC value was 6.25 μg/mL against the P. aeruginosa strain. Mann et al [ 36 ] showed that the MIC value of AgNPs against P. aeruginosa was only 3 μg/mL when the size of these nanoparticles was 2 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [ 35 ] used AgNPs with a size of 20–40 nm and noted that the MIC value was 6.25 μg/mL against the P. aeruginosa strain. Mann et al [ 36 ] showed that the MIC value of AgNPs against P. aeruginosa was only 3 μg/mL when the size of these nanoparticles was 2 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms are the extracellular matrix that is responsible for the protection of cells from different stresses, including antibiotic stress [ 15 , 29 , 39 , 44 ]. Biofilm-producing microbes have also been known for their resistance to a range of antimicrobial agents, including clinically relevant antibiotics [ 15 , 29 , 39 , 44 , 47 ]. Overexpressed efflux pump mechanism is evident from the luxuriant growth on the high concentration of Et-Br, which is evident by a higher level of fluorescence under the UV-transilluminator.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed efflux pump mechanism is evident from the luxuriant growth on the high concentration of Et-Br, which is evident by a higher level of fluorescence under the UV-transilluminator. Efflux pumps are supposed to be the key component that plays a crucial role in resistance [ 15 , 29 , 47 ]. However, in this study, the clinical isolate PS-2 was found to be highly resistant due to the coordination of MBL, efflux pump, and biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations